Deposition of high-quality Ge film on Si by PECVD using GeCl4/H2 for fabricating near-infrared photodiodes. (September 2022) - Lai, Jyun-You; Tsai, Shang-Che; Lin, Ming-Wei; Chen, Szu-yuan
Abstract: Direct deposition of high-quality Ge film on Si substrate suitable for fabricating Ge/Si photodiodes was achieved by using plasma-enhanced chemical vapor deposition (PECVD) with GeCl4 /H2 as precursors. A tensile-strained, impurity-free, monocrystalline Ge film with a surface roughness of < 1 nm and a threading-dislocation density on the order of 10 4 cm −2 could be grown at a rate of ca. 80 nm/min at a substrate temperature of 450 °C directly without the need of any kind of buffer layer or post-annealing. When applied to fabricate near-infrared (NIR) photodiodes, a low dark current density and a reasonably good responsivity for the employed photodiode architecture were attained, revealing the potential of this low-temperature fabrication method in monolithic integration of optoelectronic components with Si-based electronic circuits. The success of this technique may be attributed to an atomic-layer-deposition-like process for both nucleation and growth. Highlights: Ge is deposited on Si substrate by PECVD with germanium tetrachloride and hydrogen. Epitaxially-grown monocrystalline Ge film with tensile strain is obtained. Low threading-dislocation density and surface roughness are achieved. The Ge film is grown at low substrate temperature without need of post-annealing. The method is applied to fabrication of Ge/Si photodiode for demonstration.